Sekuritisasi TikTok di Amerika Serikat di Masa Pemerintahan Donald Trump pada tahun 2020 - Rahmadhaniah Putri Ichwan; Rizki Dian Nursita (Jisiera: The Journal of Islamic Studies and International Relations, 2023)
Donald Trump issued a policy to ban the use of the application made in China with suspicions of theft of personal data of US citizens of TikTok users and as a first step in protecting national security. Fears of data theft and espionage that Donald Trump assumes will be channeled to the Chinese government—particularly by the Chinese Communist Party, are threatening TikTok to no longer operate in the United States. Trump's speech act to the media and his statement on August 6, 2020 at the White House became the first step in America's national emergency in banning TikTok in the US. However, there have been some discussions and considerations between TikTok and Donald Trump and the US government, especially with the US Department of Commerce and the Secretary of State. By using securitization theory, the author analyzes the steps taken by Trump regarding the problems he faces. The provisional argument against this case is that Trump banned TikTok to protect his national security, especially data and at the same time cover up his campaign failure in Tulsa, Oklahoma. There is also an assumption that Trump will buy TikTok not only for reasons of national security but in order to be able to control the work of the application and have algorithm technology that is the key to the success of the application.